Edukasi Teknik Ekualisasi Penyelaman Turtle Conservation Community di Pantai Nipah Kabupaten Lombok Utara - Sabariah, Sabariah; Iing, Iing; Qamaru, Lalu Anzuru Wahiyal; Akbarsyah, Muhammad Diandra; Khairiyah, Dinur; Bendesa, I Wayan Surya Adi Pradhana; Arsana, Bagus Surya; Muhid, Abdul; Nabila, Rahma Igta; Widyadari, Ni Nengah Dirwi Bella; et al. (Jurnal Pengabdian UNDIKMA, 2025)
This community service aims to increase knowledge of Equalization techniques for Turtle Conservation Community divers in Nipah beach, North Lombok regency. The implementation method used interactive education with 15 participants. This community service activity was carried out in several stages, namely; 1). Pre-test, 2). Education using videos and posters, 3) Discussion, and 4). Post-test. Furthermore, the data obtained was analyzed using Microsoft Excel software. The results of this community service showed that the knowledge of the Nipah Turtle Conservation Community regarding diving equalization techniques increased, as evidenced by the average pre-test and post-test results obtained increasing by 25%.